PROSPECTIVE OF THE NATIONAL BUSINESS ENVIRONMENT - Flores Konja, Adrián Alejandro (2010)
Foresight has burst in the planning of business and industry, often promoted by national governments. Is conceived as an approach to a planning process involved in identifying and achieving progressively the conditions for future success, defined as the achievement of the vision of the organization. This article outlines the basics of Foresight and approaches and tools for its implementation. This article is the result of exploratory research, basically literature, whose aim is to explore the adequacy of the concepts of foresight with the characteristics of Peruvian business environment in order to optimize the application of the concept and methodology prospectively to our environment. As explained below, this relationship of the business environment and planning in the context of a National Industrial Plan and the requirements of a competitive global environment is understood more advantageously from the viewpoint of foresight.